2015
DOI: 10.1186/s13047-015-0096-3
|View full text |Cite
|
Sign up to set email alerts
|

IL‐17 cytokines in bone healing of diabetic Charcot arthropathy patients: a prospective 2 year follow‐up study

Abstract: BackgroundLittle is currently known of the pathophysiological mechanisms triggering Charcot arthropathy and regulating its recovery although foot trauma has been proposed as a major initiating factor by activation of proinflammatory cytokines leading to increased osteoclastogenic activity and progressive bone destruction. Several members of the IL-17 family of proinflammatory cytokines have been shown to play a key role in the pathogenesis of inflammatory conditions affecting bone and joints but none has previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(49 citation statements)
references
References 51 publications
0
47
1
1
Order By: Relevance
“…Such a mechanism could explain the current results showing that IL-6 and TNF-α had begun to increase shortly after TCC treatment when unfavorable healing conditions caused by continued weight-bearing on the diseased foot had ceased. A similar increase by IL-17 family cytokines shortly after TCC in Charcot patients [ 12 ] lend further support to offloading being a critical factor which interrupts the vicious cycle caused by continued weight-bearing and sets the wheels of bone repair in motion. Although it may seem paradoxical that increased activity by inflammatory cytokines is beneficial to the healing process, there is ample evidence to show that a secondary or late phase of proinflammatory mediators is in fact mandatory for bone healing to proceed normally [ 3 , 40 ].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Such a mechanism could explain the current results showing that IL-6 and TNF-α had begun to increase shortly after TCC treatment when unfavorable healing conditions caused by continued weight-bearing on the diseased foot had ceased. A similar increase by IL-17 family cytokines shortly after TCC in Charcot patients [ 12 ] lend further support to offloading being a critical factor which interrupts the vicious cycle caused by continued weight-bearing and sets the wheels of bone repair in motion. Although it may seem paradoxical that increased activity by inflammatory cytokines is beneficial to the healing process, there is ample evidence to show that a secondary or late phase of proinflammatory mediators is in fact mandatory for bone healing to proceed normally [ 3 , 40 ].…”
Section: Discussionmentioning
confidence: 87%
“…Radiographic data are presented in Table 2 . Tables 1 and 2 have in part been presented in a previous study [ 12 ]. One patient had no radiographic data after 18 months into the study as the patient chose to interrupt participation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DPSCs are located in the dental pulp, which possesses self-renewal ability and can differentiate into odontoblasts ( 4 ). Previous research has indicated that there are several factors affecting DPSC proliferation and differentiation ( 5 ). They include basic fibroblast growth factor, transforming growth factor, bone morphogenetic protein, β-phosphoglycerol and dentin ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Related to this, studies have explored the possible relationship between interleukin levels and acute Charcot foot [ 17 , 27 29 ] and found increased levels of interleukin-1 receptor antagonist (IL-1RA), tumor necrosis factor α (TNF- α ), interleukin-6 (IL-6), and interleukin-17 subtypes A, E, and F (IL-17A/E/F), as well as decreased levels of interleukin-1 β (IL-1 β ) and interleukin-8 (IL-8).…”
Section: Introductionmentioning
confidence: 99%